Tuning FRET efficiency as a novel approach for improved detection of naphthalene: application to environmental samples. Issue 7 (21st January 2016) - Nandi, Sandip; Adhikari, Sangita; Mandal, Sandip; Banerjee, Arnab; Das, Debasis
Abstract : Naphthalene has emission in the ultraviolet (UV) region, limiting its trace level determination in biological and environmental samples due to detrimental effect of UV light on the living cell and interference from other substances having emission in the UV region. Fluorescence resonance energy transfer strategy is adopted for determination of traces naphthalene in the visible region. Significant improvement of lowest detection limit of naphthalene has been achieved through tuning of fluorescence resonance energy transfer efficiency. Anthranilic acid pyrene (ANP) conjugate provides lowest detection limit for naphthalene among three probes studied, viz. ANB, aniline‐ pyrene conjugate (APA) and ANP. ANP efficiently measures naphthalene content in river water. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Ultraviolet (UV) emission limits determination of traces naphthalene in biological and environmental samples as UV light is detrimental on living cell and interferes the emissions of other substances in the UV region. Fluorescence resonance energy transfer (FRET) strategy allows determination of traces naphthalene in the visible region where low‐cost probes, viz. 2‐(benzylideneamino) benzoic acid, aniline‐pyrene conjugate and anthranilic acid pyrene (ANP) participate in the FRET process with naphthalene. Highest FRET efficiency of ANP allows lowest detection of limit for naphthalene. ANP is useful to determine naphthalene concentration of Gomti river water.